Day02. - Mak, Hon Keat. (2010)
During the years of studying animation in ADM, I have focused on pursuing in specialized skill sets; such as character animation- the ability to create believable and interesting performance, 3D modeling- to create believable detailed characters, texturing and lighting- to create mood and also bring believability to the overall feel. But it all came to a point where I ask myself, why do I seek to achieve such believability and for what purpose? The answer was obvious but somehow elusive, that is to assist me in communicating with the world visually. My voice, my ideas, my stories, what I am eager to share with the world. So for communicating it is, and thus in this project, I seek to utilize all the knowledge I have learnt in my years in ADM, to tell a story visually.